The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00531-008-0412-2
|View full text |Cite
|
Sign up to set email alerts
|

The Ereendavaa Range (north-eastern Mongolia): an additional argument for Mesozoic extension throughout eastern Asia

Abstract: International audienceMesozoic rift basins locally bounding metamorphic core complexes have been recognized in Transbaikalia and northern China. Numerous basement outcrops located between these two regions, in eastern Mongolia, are considered as pre-Palaeozoic in age. One of these, the Ereendavaa Range, appears as a gneissic core marked by amphibolite-facies metamorphic conditions. The range is overlain to the NW by the unmetamorphosed Mesozoic Onon Basin. Below the basin, the upper part of the range consists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 60 publications
1
40
0
Order By: Relevance
“…Because detailed geochronological work is lacking, the extensional period is imprecisely defined between the 135 and 120 Ma in the Transbaikalia-MongoliaGreat Xing'an range and North margin of the South China block (Figs. 16, 17;Donskaya et al, 2008;Daoudene et al, 2009Daoudene et al, , 2011Zhu et al, 2010;Ji et al, 2011). On the contrary, in the Eastern QinglingDabieshan and Yinshan-Yanshan belt, it seems that the peak of extensional tectonics took place during 130-125 (Fig.…”
Section: Cretaceous Extension In the Eastern Part Of The Eurasian Conmentioning
confidence: 92%
See 1 more Smart Citation
“…Because detailed geochronological work is lacking, the extensional period is imprecisely defined between the 135 and 120 Ma in the Transbaikalia-MongoliaGreat Xing'an range and North margin of the South China block (Figs. 16, 17;Donskaya et al, 2008;Daoudene et al, 2009Daoudene et al, , 2011Zhu et al, 2010;Ji et al, 2011). On the contrary, in the Eastern QinglingDabieshan and Yinshan-Yanshan belt, it seems that the peak of extensional tectonics took place during 130-125 (Fig.…”
Section: Cretaceous Extension In the Eastern Part Of The Eurasian Conmentioning
confidence: 92%
“…Namely, 1) west-directed subduction of a Paleo-Pacific plate during the Mesozoic causes intra-or back-arc extension (Watson et al, 1987;Traynor and Sladen, 1995;Ren et al, 2002); 2) roll-back of the westward subducting Paleo-Pacific oceanic plate, and post-orogenic collapse is following the Late Jurassic to Early Cretaceous contraction ; 3) South-Southeast-directed subduction of the Mongol-Okhotsk oceanic plate during the Mesozoic is responsible for extension (Wang et al, 2002); 4) interaction between the Pacific Zorin, 1999); Buteel (Mazukabzov et al, 2006;Donskaya et al, 2008); Nartyn (magmatic dome, Daoudene et al, 2009), Zagan (Donskaya et al, 2008); Ed (Ereendavaa, Daoudene et al, 2009Daoudene et al, , 2011; Cb (Central basement uplift of Songliao basin, Zhang et al, 2000); Xy (Xiuyan magmatic dome, Lin et al, 2007); Yg (YaganOnch Hayrhan, Zheng et al, 1991;Webb et al, 1999); Hohhot (Davis et al, 2002;Davis and Darby, 2010); Kl (Kalaqin magmatic dome, Han et al, 2001); Ym (Yunmengshan, Zheng et al, 1991;Davis et al, 1996Davis et al, , 2002; Yw (Yiwulüshan, Darby et al, 2001Darby et al, , 2004Lin and Wang, 2006); Xs (Xishan pluton, Wang et al, 2011c); Gd (Gudaoling syntectonic granite, Guan et al, 2008;Lin et al, 2011); Sl (South Liaodong Peninsula, Yin and Nie, 1996;Liu et al, 2005;Lin and Wang, 2006;Lin et al, 2008); Np (Nampho magmatic dome, Wu et al, 2007); Lg (Linglong-Guojialing complex dome, Charles et al, 2011); Jn (Jiaonan extensive dome, Hacker et al, 2009)…”
Section: Cretaceous Extension In the Eastern Part Of The Eurasian Conmentioning
confidence: 99%
“…It is noteworthy that Late Jurassic-Early Cretaceous age for extension has recently been described in Mongolia for MCC (e.g. Ereendavaa Range; Daoudene et al, 2009). In Liaoning Province, the Songliao basin exhibits Late Jurassic sediments (J3: 160-145 Ma) deposited during an extensive setting for this period (Chen et al, 1999;Lin et al, 2003).…”
Section: Timing and Tectonic Historymentioning
confidence: 95%
“…NW-SE extensional kinematics deduced from our structural study are in good agreement with similar structures already recognized over eastern Asia. They may be summarized as follows: (1) Late Mesozoic synkinematic plutons with magmatically oriented core and mylonitic rim associated with the coeval development of ductile extensional shear zones (Lin et al, 2007), and (2) several MCC, such as the Yunmengshan in north of Beijing (Davis et al, 1996), the Yiwulüshan and the South Liaodong in Liaoning Province (Darby et al, 2004;Liu et al, 2005;respectively), and as far as the Ereendavaa Range in eastern Mongolia (Daoudene et al, 2009).…”
Section: Geodynamic Implications For the Extensional Eventmentioning
confidence: 98%
“…Secondly, numerous studies demonstrated that regional extension in Russian Transbaikalia, East Mongolia and NE China mostly likely initiated during Late Jurassic (150-145 Ma) and peaked at Early Cretaceous (140-120 Ma), as indicated by occurrences of the Cretaceous metamorphic core complexes (Donskaya et al, 2008;Daoudene et al, 2009Daoudene et al, , 2011Wang T. et al, 2012), the rifting basins (Ren et al, 2002;Meng, 2003;Meng et al, 2003) …”
Section: Geological Significance Of Jurassic (170-160 Ma) Metamorphismmentioning
confidence: 99%